Capacity for Survival: Exploring Strengths of Homeless Street Youth - Bender, Kimberly (2007)
The majority of research on homeless youth has focused on the multitude of problems faced by this vulnerable population. The current study, while acknowledging the hazards of life on the streets, seeks to explore the personal strengths and informal resources street youth rely on to navigate their environments. Qualitative data from seven focus groups conducted with street youth ages 18–24 were analyzed using content analysis. These data, rich with interactions among youth participants, highlight three important themes: developing “street smarts,” existence of personal strengths, and informal resources relied upon by youth to survive. Results provide valuable insights into the strengths of homeless youth that can be useful to providers in assessing street youths’ service needs and increasing the likelihood of long-term positive outcomes.